A Novel Two-Dimensional Wind Speed and Direction Measurement Method Based on NTC - Soukar, Noura; Yazgan, Ayhan (Fırat University, 2025)
Traditional wind sensors, such as cup, hot wire, ultrasonic, and laser Doppler anemometers, often have mechanical parts that limit sensitivity, accuracy, and durability, unlike thermal flow sensors, which detect the wind by measuring the temperature variations using a heater. In addition, the methods reported in the literature have different advantages and disadvantages. In this study, different thermal flow sensor designs reported in the literature are examined and a new method based on the 2-dimensional NTC thermistor is proposed. Simulation results of the proposed method are presented. According to the results actual and calculated wind speed measurements well matched and the maximum wind speed error observed is less than %3. In addition, a simple testbed is presented for wind direction measurement.

Geleneksel rüzgâr sensörleri, bir ısıtıcı kullanarak sıcaklık değişimlerini ölçerek rüzgârı algılayan termal akış sensörlerinin aksine, kupalı, ultrasonik ve lazer Doppler anemometre gibi, genellikle hassasiyet, doğruluk ve dayanıklılığı sınırlayan mekanik parçalara sahiptir. Bunların yanında, literatürde rapor edilen yöntemlerin farklı avantajları ve dezavantajları bulunmaktadır. Bu çalışmada ise, literatürde rapor edilen farklı termal akış sensörü tasarımları incelenmiş ve 2 boyutlu NTC sensörünü temel alan yeni bir yöntem önerilmiştir. Önerilen yöntemin simülasyon sonuçları sunulmuştur. Sonuçlara göre gerçek ve hesaplanan rüzgâr hızı ölçümleri iyi bir şekilde eşleşmiştir ve gözlenen maksimum rüzgar hızı hatası %3’ten azdır. Ek olarak rüzgâr yönünün tespiti için basit bir düzenek de sunulmuştur.
NTC Tabanlı Yeni Bir İki-Boyutlu Rüzgar Hızı ve Yönü Ölçüm Yöntemi
Keywords: Electronics; Elektronik; Electronic Sensors; Elektronik Algılayıcılar